Extraction of dragon fruit foliage as natural coagulant for water treatment. - Shafad, Mohd Raside; Ahamad, Intan Salwani; Idris, Azni; Zainal Abidin, Zurina (2012)
This study presents the extraction of dragon fruit foliage for application in water treatment. Two types of extraction methods were used which are distilled water and salt extraction method. The experiments were done using jar test method. The finding shows that distilled water extraction method was more effective as compared to salt extraction method in term of turbidity removal. Therefore, distilled water extraction method had been selected for further investigation using surface water study. A comparison study was done by comparing surface water treatment by using dragon fruit foliage against alum to see the capability of dragon fruit foliage in removing turbidity. The results revealed that the turbidity removal for dragon fruit foliage using distilled water extraction was 91.9% at the dosage of 10 mg/L while for alum the turbidity removal was 99.8% at the dosage of 40 mg1L. It was found that the turbidity removal of dragon fruit foliage distilled water extraction was high and almost comparable with commercial alum and the optimum dosage for dragon fruit foliage was 4 times lower than alum. Hence, it can be concluded that dragon fruit foliage deserves evaluation as potential coagulant.